MEDIA PEMBELAJARAN MULTIMEDIA INTERAKTIF BERBASIS ADOBE PREMIERE PRO UNTUK PROSES KEGIATAN PEMBELAJARAN - Afiyati Afiyati; Sabar Rudiarto; Anis Cherid (Universitas Mercu Buana, 2022)
The purpose of the research was to find out the description of the process of making interactive multimedia based on Adobe Premiere Pro on Basic Competency in Managing the process of teaching and learning activities carried out at SMP Negeri 215 West Jakarta. This type of research uses the ADDIE research model (Analysis, Design, Develop, Implement, and Evaluate), but the author only adopts two stages, namely: analysis and design. This event was attended by 20 West Jakarta SMPN 215 teachers. The implementation of this event uses an approach method, namely presentation of material provided by the speaker, question and answer if there are socialization participants who still do not understand how Adobe Premiere Pro works. Based on the results of the Pretest and Posttest, it shows that after this socialization seminar all teachers can understand the use of Adobe Premiere Pro for making video processing programs that have 45 video effects and 12 audio effects that are used to change display patterns and create video and audio animations that you want to give to students. their students.